40 PRLR and PCCA variants associated with hair length in Brangus heifers. (30th November 2020) - Davila, Kaitlyn M Sarlo; Howell, Alyssa; Nunez, Andrea; Orelien, Arseia; Roe, Victoria; Rodriguez, David; Rodriguez, Eduardo; Dikmen, Serdal; Mateescu, Raluca G
Abstract: Thermal stress limits beef cattle production and results in a loss of 370 million in the U.S. annually due to reduced animal performance. A shorter hair coat is a key thermoregulative adaptation that allows cattle to lose heat more efficiently through conductive, convective, and evaporative cooling at the hair-skin interface. The objective of this study was to identify genetic variants associated with the length of the topcoat and undercoat of cattle. Hair samples were collected from the shoulder, 4 inches down from the spine from 2, 161 heifers in 2016, 2017 and 2018. ImageJ software was used to measure hair length. The length of the topcoat and undercoat were evaluated for each individual by averaging five long and five short hairs, respectively. DNA was extracted from blood samples and genotyped with the Bovine GGP F250 array. After quality control, 132, 225 SNP were available for association analyses using Golden Helix SVS. Year of collection was fitted as a fixed effect and the genomic relationship matrix was fitted to account for the genetic covariance among animals. To correct for multiple tests, the Benjamini-Hochberg false discovery rate was constrained to 0.1. Four SNP in the PRLR gene were significantly associated with topcoat length, including a missense mutation that explained 4% of the variation in topcoat length. PRLR has previously been demonstrated to significantly impact hair length in cattle. Seven SNP in the PCCA gene were significantly associated with undercoat length. PCCA belongs to the biotin transport and metabolism pathway. Biotin deficiency has been reported to cause hair loss. These genetic variants may contribute to a shorter hair coat and more thermotolerant animals.